ANALISIS KESUKSESAN APLIKASI BRIMO DENGAN PENDEKATAN MODEL DELONE AND MCLEAN - Lusiana Marselina; Ismi Kaniawulan; H. Dayan Singasatia (Jurnal Informatika Teknologi dan Sains, 2022)
Bank Rakyat Indonesia (BRI) is one of the largest state-owned banks in Indonesia. Bank BRI provides a Mobile Banking facility called "BRImo". Problems in the BRImo Application even though it provides convenience in online transactions, there are still some users who experience problems using the BRImo application. Such as difficulties in using the BRImo Application, difficulties in registering for BRImo, unable to login, and sometimes users are often blocked. The complaint is an inconvenience in using the BRImo Application so that it can reduce the level of user trust. The purpose of this study is to determine the level of success of the BRImo application and which variables affect user satisfaction. The research methodology uses quantitative methods and this study uses 5 variables from the DeLone and McLean method, namely: System Quality, Information Quality, Service Quality, User Satisfaction, and Net Benefits. The results of this study are System Quality, Information Quality has a significant effect on user satisfaction and user satisfaction has a significant effect on net benefits.